(3QSGdI aj GdefWbs - (3GKjQ GdOjf GdGHgQis; (3eMeO Hf CHj HcQ Hf CMeO GdTdj HGYdhj,J (B1094 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg QSGdI ai GdefWb ChQOfG ajgG eG HMK EjSGZhLi GddaX GdOGd HGdhVY jOd Ydi eG hVY dg s
(3BNQgG (B:s
(3cbhdfG GdhGMO jUa ddEKfjf hGdcd CYXe ef GdLRA BNQ GdQSGdI JeJ s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(4196(6)) s
Keywords: (3GdadSaI hGdefWbs